Churchill [videorecording] the man - Ashwood, Terry ([S.l.] Associated British-Pathe Production, 1990)
Winston Churchill rallied the British to victory in World War II. He was a World War II P.O.W. who later became a Prime Minister of Great Britain. Presents his bolstering British forces, addressing the U.S. Congress and conferring with Roosevelt and Stalin at Yalta. It also presents the destruction of London, the Battle of Britain, excerpts from Churchill's memorable speeches and his funeral procession.
VHS.
Credits : Spoken by Emilyn Williams ; commentary written by John Pudney.
Keywords: Churchill, Winston -- Sir -- 1874-1965.; Heads of state -- Great Britain -- Biography; Great Britain -- History -- 20th century